2010
DOI: 10.1155/2011/620984
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Effects of a 180 mT Static Magnetic Field on Bone Mineral Density of Osteoporotic Lumbar Vertebrae in Ovariectomized Rats

Abstract: The effects of a moderate-intensity static magnetic field (SMF) on osteoporosis of the lumbar vertebrae were studied in ovariectomized rats. A small disc magnet (maximum magnetic flux density 180 mT) was implanted to the right side of spinous process of the third lumbar vertebra. Female rats in the growth stage (10 weeks old) were randomly divided into 4 groups: (i) ovariectomized and implanted with a disc magnet (SMF); (ii) ovariectomized and implanted with a nonmagnetized disc (sham); (iii) ovariectomized al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 69 publications
0
28
1
5
Order By: Relevance
“…Finally, because SMF is a single physical factor, it can result less side effects comparing with varieties of physical factors such as PEMF. Since SMF has been shown to be effective in facilitating ununited fracture repair 16) and preventing bone loss 17) , it has received considerable attention about the biological effect of SMF on bone cells. A certain intensity SMF has been reported that it can significantly enhance osteoblast differentiation in vitro [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because SMF is a single physical factor, it can result less side effects comparing with varieties of physical factors such as PEMF. Since SMF has been shown to be effective in facilitating ununited fracture repair 16) and preventing bone loss 17) , it has received considerable attention about the biological effect of SMF on bone cells. A certain intensity SMF has been reported that it can significantly enhance osteoblast differentiation in vitro [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…overektomi yaparak osteoporotik hale getirilen ratlarda vertebraya yerleştirilen disk şeklindeki mıknatısların kemiğin mineral dansitesini arttırdığını bildirmişlerdir. 2 Altay ve ark. titanyum kaplı SmCo mıknatısların köpek mandibulasına implantasyonundan altı ay sonrasına kadar takip ettikleri ça-lışmalarında, herhangi bir osteoblastik ya da yara iyileşmesine olumsuz etki göstermediğini ve hücre hacminde şekil içeriğinde dikkate değer bir değişiklik olmadığını bildirmişlerdir.…”
Section: Stati̇k Manyeti̇k Alanin Kemi̇k üZeri̇ne Etki̇leri̇unclassified
“…2 Bu nedenle SMA, artrit, kronik ağrı sendromu, yara iyileşmesi, uykusuzluk (insomnia), baş ağrısı gibi spesifik medikal problemlerin tedavisinde son yıllarda kullanımı artan bir tedavi seçeneği haline gelmiştir. 4 SMA oluşturan mıknatıslardan medikal tedavide en çok "rare earth magnets" adı verilen "Samariyum-kobalt (SmCo)" ve "neodimiyum-ironboron" adlı mıknatıslar kullanılmaktadır.…”
unclassified
See 2 more Smart Citations